Characteristics of alpha males in Nepal gray langurs. Issue 7 (26th June 2015) - Borries, Carola; Perlman, Rachel F.; Koenig, Andreas
Abstract : In species with strong male‐male competition, access to females in multimale‐multifemale groups is usually regulated via a dominance hierarchy. The highest ranking (alpha) male often has priority of access and sires most offspring. The alpha male can change in three basic ways: (i) a recent immigrant or a resident challenges and becomes the new alpha; (ii) formation of a new group; (iii) succession—becoming alpha after higher ranking males have left. When, in a given primate population, the alpha male changes in different ways, two questions arise: (a) which is the most successful tactic and (b) do male attributes, such as age, aggressiveness or propensity to commit infanticide, affect the outcome? We examined these questions in the seasonally breeding Nepal gray langurs ( Semnopithecus schistaceus ) at Ramnagar, where new alpha males were either recent immigrants or residents. Success was measured as alpha tenure, residency duration, and the number of offspring sired (paternity exclusion based on DNA analysis, 28 infants). We documented 12 alpha‐male tenures across two multimale‐multifemale groups between 1991 and 1997. The predominant mode of change was the immigrant tactic. Age had no effect perhaps because alpha males were among the youngest adult males in their group. As expected, infanticidal males performed similarly to non‐infanticidal ones. Alpha tenure was highly variable and longer for immigrant alphas and hyper‐aggressive ones. However, none of the tactics or attributes examined resulted in significantly longer residencies or more offspring, likely because of the timing of immigrations and stochastic effects (i.e., the number of conceptions occurring per alpha tenure). The influence of female mate choice on male reproductive success requires further investigation. Furthermore, it remains to be examined why resident alpha males—with their presumed better knowledge of their opponents —performed so poorly. Am. J. Primatol. 79:e22437, 2017. © 2015 Wiley Periodicals, Inc.